The Way of Logic into Mathematics - Peckhaus, Volker (Theoria. Segunda Época (Seccion monografica Sobre la historia de la lógica matemática, hg. v. Luis Vega Reñon))
Abstract: Philosopher’s Index 31.3 (1997), 206; Zbl. Math. 914.01008 (L. Harkleroad). Rezensionen: MR 98c:01028 (E. Glas).

The Axiomatic Method and Ernst Schröder’s Algebraic Approach to Logic - Peckhaus, Volker (Philosophia Scientiae. Travaux d’histoire et de philosophie des science (Nancy) 1/3 (1996). 1–15 [erschienen im Juni 1997, = Actes du congrès International Poincaré – Nancy 1994; Bd. 2.2])

Application of Neural Networks for Control of Four-Quadrant Converters in Railway Propulsion Systems Applications of Neural Adaptive Control Technology - Scheffler, Sebastian; Böcker, Joachim (Applications of Neural Adaptive Control Technology)

Witold Marciszewski/Roman Murawski. Mechanization of Reasoning in a Historical Perspective. Amsterdam/Atlanta, GA: Rodopi 1995. (Poznań Studies in the Philosophy of the Sciences and the Humanities; 43) - Peckhaus, Volker (Modern Logic)

Jarmo Pulkkinen, The Threat of Logical Mathematism. A Study on the Critique of Mathematical Logic in Germany at the Turn of the 20th Century. Peter Lang: Frankfurt a.M. 1994 (= Scandinavian University Studies in the Humanities and Social Sciences; 7) - Peckhaus, Volker (History and Philosophy of Logic)

Ein automatisiertes Verfahren zur Off-line-Identifikation der elektrischen Parameter von pulswechselrichtergespeisten Asynchronmotoren - Ruff, M.

Beiträge zur Entwicklung von Gleichstromumrichtern mit geringer Ausgangsspannung - Fiedler, A.

Excitons with anisotropic effective mass - Schindlmayr, Arno (European Journal of Physics)
We present a simple analytic scheme for calculating the binding energy of excitons in semiconductors that takes full account of the existing anisotropy in the effective mass, as a complement to the qualitative treatment in most textbooks. Results obtained for excitons in gallium nitride form the basis for a discussion of the accuracy of this approach.

Violation of particle number conservation in the GW approximation - Schindlmayr, Arno (Physical Review B)
We present a nontrivial model system of interacting electrons that can be solved analytically in the GW approximation. We obtain the particle number from the GW Green’s function strictly analytically, and prove that there is a genuine violation of particle number conservation if the self-energy is calculated non-self-consistently from a zeroth order Green’s function, as done in virtually all practical implementations. We also show that a simple shift of the self-energy that partially restores self-consistency reduces the numerical deviation significantly.

[Rez. v.] Luigi Marino. Praeceptores Germaniae. Göttingen 1770–1820. Aus dem Italienischen v. Brigitte Szabó-Bechstein. Göttingen. Vandenhoeck & Ruprecht 1995 - Süßmann, Johannes (Archiv für Sozialgeschichte)